Influence of the intrinsic properties of nanopipettes on sensing performance - Wenhao Ma; Rong Tian; Shixuan He; Shaoxi Fang; Bohua Yin; Yongjia Wang; Ting Weng; Wanyi Xie; Danqun Huo; Changjun Hou; Deqiang Wang (Chemical Engineering Journal, 2026)

A multimethod analytical technique based on FT–ICR MS elucidates the thermal transformation characteristics of DOM in fecal sludge biochar and its effects on seed germination - Changjun He; Nana Liu; Wei Meng; Yuxuan Li; Xiaoqin Zhou; Shikun Cheng; Zifu Li (Journal of Environmental Chemical Engineering, 2026)

A cross-reactive colorimetric sensor array based on AuAg nanocluster–Au nanoparticle interactions for sulfide sensing and Baijiu classification - Yinjiang Leng; Jing Zhang; He Li; Yi Ma; HuiBo Luo; Danqun Huo; Changjun Hou (Food Chemistry, 2026)

Response of Nitrogen Removal and Florfenicol Degradation in Multi-Soil-Layering Systems Treating Antibiotic-Stressed Rural Wastewater - Rui Wang; Zhiqiang Chen; Shijie Zheng; Xiaoliang Zhang; Jinhong Xie; Pan Li; Changjun Chen; Yihui Mao; Zhouliang Tan; Yang He (Water, Air, & Soil Pollution, 2026)

Effects of sidewall friction on the structural style and deformation evolution of fold-and-thrust belts: analog modeling results - Wengang He; Weiping Feng; Changjun Ji (Journal of Geodynamics, 2026)

Microplastics form a dispersal-limited artificial niche that selectively enriches potential plastic-degrading bacteria and pathogens in coastal aquaculture systems - Xuri Dong; Yanru He; Changjun Li; Ruiming Wu; Li Chen (Marine Pollution Bulletin, 2026)

Integrated three-process system for waste valorization: Catalyst-free photoreductive H2O2 synthesis, calcium-containing COD wastewater treatment and calcium peroxide production - Hanhao Zhou; Pan Wu; Jian He; Changjun Liu; Wei Jiang (Journal of Environmental Chemical Engineering, 2026)

Microbial degradation of plastics in the environment: Mechanisms, enzymatic pathways, and constraints from laboratory studies to environmental reality - Xuri Dong; Lixin Zhu; Yanru He; Changjun Li; Ruiming Wu; Daoji Li (Journal of Environmental Management, 2026)

Microwave assisted anaerobic digestion of waste-activated sludge: Integrating multi-scale characterisation and energy assessment for enhanced biogas recovery - Yuxuan Li; Changjun He; Luiza C. Campos; Shikun Cheng; Zifu Li; Yukun Hu (Environmental Research, 2026)

Microplastics selectively enrich potential plastic-degrading bacteria in estuaries - Xuri Dong; Yanru He; Changjun Li; Qingqing Li; Lixin Zhu; Daoji Li (Marine Pollution Bulletin, 2026)

From AI modelling to validation: A 10-day pipeline for potential lead compounds validation - Bin Chen; Yuan Hu; Wen He; Guo Li; Ruiqi Liu; Jiawei Li; Xiujuan Li; Lingling Wei; Aiguo Gu; Song Yang; Changyang Chen; Xiushi Song; et al. (Pesticide Biochemistry and Physiology, 2026)

RUNX1 promotes NSCLC progression by ACP5/SMAD3-mediated M2 macrophage polarization - Changjun He; Yingbin Li; Nianyu Gao; Bicheng Fu; Fucheng Zhou; Boxiong Ni; Jianlong Bu; Junhui Chen; Xianglong Kong; Pengju Li (Inflammation Research, 2025)

Optimizing phosphorus management in subtropical red soil sloping croplands: The synergistic effects of contour cultivation and straw return - Ying Zhang; Ji Liu; Longtao Li; Changjun Li; Pofei Wang; Zhongxiang He; Peng Cheng; Jianjun Luo; Hua Peng; Jian Zhu (Agriculture, Ecosystems & Environment, 2025)

Sustainable recovery of Te(IV)/Se(IV) from mixed solutions via selective adsorption-desorption on amorphous hydrous zirconium oxides: Synergistic purification and enrichment - Biao Yuan; Pan Wu; Changjun Liu; Jian He; Wei Jiang (Chemical Engineering Journal, 2025)

Transport mechanism of microplastics from a still water system to a dynamic estuarine system: A case study in Macao SAR - Qingqing Li; Lixin Zhu; Nian Wei; Mengyu Bai; Kai Liu; Xiaohui Wang; Chunhua Jiang; Changxing Zong; Feng Zhang; Changjun Li; Xuri Dong; Yinan He; et al. (Marine Pollution Bulletin, 2025)

Triple binding pockets of AtSDH: Reduced affinity underpins SDHI- resistance in Alternaria tenuissima - Bin Chen; Ruiqi Liu; Wen He; Yuan Hu; JiaWei Li; Xiujuan Li; Aiguo Gu; Song Yang; Changyang Chen; Xiushi Song; Changjun Chen; Wenyong Shao (Pesticide Biochemistry and Physiology, 2025)

Unveiling the dynamic viral landscape across developmental stages of cold seep ecosystems: Implications for global marine biogeochemistry - Yuanyuan Wang; Shanzi Huang; Jian He; Zhengqi Feng; Wenbo Wu; Changjun Guo; Jianguo He (Journal of Hazardous Materials, 2025)

Bifunctional chitosan-modified urea–formaldehyde fertilizer for soil restoration and slow, sustained nitrogen release - Zhenglu Yang; Biao Yuan; Pan Wu; Jian He; Changjun Liu; Wei Jiang (Environmental Research, 2025)

Target inhibition of rolling circle amplification generates G43 long nanowires for reverse signaling determination of alkaline phosphatase - Shuyu Zhu; Shiying Zhou; Liyuan Deng; Jiangbo Dong; Tao Gu; Xinyu He; Liang Jin; Changjun Hou; Danqun Huo (Analytica Chimica Acta, 2025)

Megalocytivirus: A Review of Epidemiology, Pathogenicity, Immune Evasion, and Prevention Strategies - Changjun Guo; Jian He; Xiaopeng Xu; Shaoping Weng; Jianguo He (Reviews in Aquaculture, 2025)
Megalocytivirus, a large double‐stranded DNA virus belonging to the Iridoviridae family, has infected over 100 species of fish, leading to significant economic losses in the aquaculture, food, and ornamental fish industries. These viruses exhibit icosahedral symmetry and have diameters ranging from 120 to 200 nm. Two distinct viral species of genus Megalocytivirus have been identified: Megalocytivirus pagrus 1 and Megalocytivirus lates 1 . Megalocytivirus pagrus 1 encompasses three distinct genotypes: infectious spleen and kidney necrosis virus, red seabream iridovirus, and turbot reddish body iridovirus, whereas Megalocytivirus lates 1 comprises a single genotype, known as scale drop disease virus. Infection with Megalocytivirus pagrus 1 is a notifiable disease to the World Organisation for Animal Health. Over the past two decades, significant progress has been made in various aspects of megalocytivirus biology, including the understanding of its molecular genetics, transmission modes, host ranges, pathogenic mechanisms, diagnostic methodologies, and vaccines. This review provides a comprehensive overview of the current understanding of megalocytiviruses, focusing on its epidemiology, pathogenicity, immune evasion, and prevention strategies for fish infected with megalocytiviruses. We hope that these findings will provide new insights in the development of effective prevention and control strategies for megalocytiviral diseases.

Regulating organic loading to mitigate the impact of microplastics on nitrogen removal and microbial communities in SBR systems - Yi Yang; Lin Luo; Jian Zhu; Kai Deng; Changjun Li; Ying Zhang; Zhongxiang He; Pofei Wang; Hua Peng (Journal of Water Process Engineering, 2025)

Highly effective adsorption of As(III) and As(V) via zirconium-based materials with abundant active groups and capacity - Biao Yuan; Pan Wu; Changjun Liu; Jian He; Wei Jiang (Chemical Engineering Journal, 2025)

Rapid green degradation of ethylene glycol-based antifreeze wastewater via a coupled photolytic and photocatalytic double-pathway mechanism - Yiheng Wang; Meng Liu; Qi Miao; Pan Wu; Jian He; Changjun Liu; Wei Jiang (Journal of Water Process Engineering, 2025)

Establishment and characterization of a novel cell line derived from spotted sea bass Lateolabrax maculatus and its susceptibilities to iridoviruses - Zhipeng Zhan; Xueqian Cao; Jie Su; Yangchi Cui; Yang Zheng; Pengli Xiao; Zhoutao Lu; Shaoping Weng; Changjun Guo; Jianguo He (Aquaculture, 2025)

Hydrothermal treatment of septic sludge: Revealing temperature-sensitive dissolved organic matter and potential toxicity relationships in the hydrothermal liquid - Wei Meng; Lei Zheng; Changjun He; Shikun Cheng; Zifu Li (Journal of Environmental Management, 2025)

Preparation of “dry water”-type liquid marbles with enhanced mechanical stability and CO2 capture performance - Jian He; Yifan Liang; Wenting Xiang; Changjun Liu; Pan Wu; Wei Jiang (Chemical Engineering Journal, 2024)

Distinct impacts of microplastics on the carbon sequestration capacity of coastal blue carbon ecosystems: A case of seagrass beds - Xin Hou; Changjun Li; Yong Zhao; Yike He; Wentao Li; Xiaotong Wang; Xianhua Liu (Marine Environmental Research, 2024)

Characterization of metal-binding behavior of DOM component structure in biochar: Analysis of binding sites, binding sequences and impact pathways - Changjun He; Nana Liu; Wei Meng; Zifu Li (Journal of Environmental Chemical Engineering, 2024)

Effective stiffness matrix calculation of geocell layer and reinforcement mechanism analysis of geocell reinforced embankment - Changjun Yin; Jingjing He; Ahmed Adam Khalifa Gowi; Zhuo Li; Chenhang Zhou (Geotextiles and Geomembranes, 2024)

Estimation of wheat protein content and wet gluten content based on fusion of hyperspectral and RGB sensors using machine learning algorithms - Shaohua Zhang; Xinghui Qi; Mengyuan Gao; Changjun Dai; Guihong Yin; Dongyun Ma; Wei Feng; Tiancai Guo; Li He (Food Chemistry, 2024)

Intelligent treatment of tannery wastewater via H2O2 photocatalytic oxidation coupled adsorption process - Huimin Yu; Miaomiao Tang; Jian He; Changjun Liu; Pan Wu; Wei Jiang (Journal of Water Process Engineering, 2024)

Mechanical properties and constitutive model of high-abundance methane hydrates containing clayey–silt sediments - Fan Yang; Changjun Li; Na Wei; Wenlong Jia; Jie He; Shuoshuo Song; Yuanrui Zhang; Youzhi Lin (Ocean Engineering, 2024)

Inhibiting advanced glycation end products (AGEs) of high-performance hemodialysis membranes self-assembled by gallic acid and Ti3C2Tx MXene - Qiqi Wang; Changjun Mu; Ya'nan Yu; Xia Feng; Yang He; Li Chen (Chemical Engineering Journal, 2024)

Nb2CTx MXene coating with inhibition of oxidative stress prepared by Marangoni effect for hemodialysis therapy - Yang He; Hanshu Sun; Yanjie Wang; Ya'nan Yu; Changjun Mu; Li Chen (Chemical Engineering Journal, 2024)

Ecological performance of an integrated ex-situ rice-fish co-culture system - Qiao Liu; Leji Zhang; Yi Yang; Jiacen Zou; Yipeng Yang; Jiayu Ge; Haoxiao Yan; Kuo He; Changjun Yang; Rabia Tahir; Liulan Zhao; Song Yang (Aquaculture, 2024)

Financial innovation, green investment, and sustainable mineral extractions in China - Guohua He; Peiling Zhu; Changjun Wu (Resources Policy, 2024)

From pollution to solutions: Insights into the sources, transport and management of plastic debris in pristine and urban rivers - Yinan He; Jungang Lu; Changjun Li; Xiaohui Wang; Chunhua Jiang; Lixin Zhu; Xinyu Bu; Khalida Jabeen; TuanLinh Tran Vo; Daoji Li (Environmental Research, 2024)

New insights into the effect of pyrolysis temperature on the spectroscopy properties of dissolved organic matter in manure-based biochar - Xinran Liu; Lihong Wei; Jinyuan Jiang; Changjun He; Xun Sun; Haoyang Song (Environmental Science and Pollution Research, 2024)

NtERF4 promotes the biosynthesis of chlorogenic acid and flavonoids by targeting PAL genes in Nicotiana tabacum - Shun He; Xin Xu; Qian Gao; Changjun Huang; Zhaopeng Luo; Pingping Liu; Mingzhu Wu; Haitao Huang; Jun Yang; Jianmin Zeng; Zhong Wang (Planta, 2024)

Ultrasensitive detection of circulating tumor cells via DNA walker driven by a DNA circuit synergized with MOF-on-MOF nanozyme - Jiaying Zhao; Yanyi Long; Congjuan He; Yinjiang Leng; Zhen Huang; Yi Ma; Changjun Hou; Danqun Huo (Chemical Engineering Journal, 2024)

Development and characterization of a spleen cell line from yellowfin seabream Acanthopagrus latus and its susceptibility to Mandarinfish ranavirus - Zhipeng Zhan; Jiajie Fu; Huiquan Chen; Hongbo Pan; Shaoping Weng; Jianguo He; Changjun Guo (Journal of Fish Diseases, 2023)
Yellowfin seabream ( Acanthopagrus latus ) is one of the most commercially important marine fish in China. In this study, a new continuous cell line, named ALS cells, was developed from the spleen tissue of A. latus . The cell line was maintained in Dulbecco's modified Eagle medium/Nutrient Mixture F‐12 Ham (DMEM/F‐12) supplemented with 10% fetal bovine serum (FBS) and successfully cultured up to 50 passages. The cell line was authenticated by amplifying and sequencing mitochondrial cytochrome C oxidase subunit‐I ( coi‐I ) gene. The ALS cell line had the maximum growth rate in DMEM/F‐12 medium containing 20% FBS at 27°C. Chromosome number analysis showed that the ALS cells have a modal diploid chromosome number of 34. The ALS cell line was transfected with the pEGFP‐N1 plasmid, and green fluorescence was observed. The ALS cell line was used for testing Mandarinfish ranavirus (MRV) susceptibility, and the cytopathic effects in the cell line were observed at 4 days post‐infection (dpi). Furthermore, the susceptibility of the ALS cell line to MRV and the levels of MRV mRNA and viral loads were found to be significantly increased at 1–7 dpi. This study revealed that the ALS cell line could be useful for molecular, virological, and biotechnological studies on yellowfin seabream.

3D DNAzyme walker based electrochemical biosensor for attomolar level microRNA-155 detection - Jiaying Zhao; Congjuan He; Yanyi Long; Jincan Lei; Huan Liu; Jingzhou Hou; Changjun Hou; Danqun Huo (Analytica Chimica Acta, 2023)

Salinity significantly reduces plastic-degrading bacteria from rivers to oceans - Xuri Dong; Lixin Zhu; Yanru He; Changjun Li; Daoji Li (Journal of Hazardous Materials, 2023)

Duplex-specific nuclease powered 3D DNA walker and quantum dots barcodes for homogeneous electrochemical detection of microRNAs - Jiaying Zhao; Congjuan He; Huisi Yang; Yanyi Long; Jiangbo Dong; Li Wen; Zhikun Hu; Xinxue Yin; Changjun Hou; Danqun Huo (Analytica Chimica Acta, 2023)

A new cavitation model for simulating steady and unsteady cavitating flows - Jie He; Changjun Li; Wenlong Jia; Bolin Qiu; Fan Yang; Caigong Zhang (Ocean Engineering, 2023)

Treatment of Pyrolytic Eco-toilet Waste: Characterization of Feces-Based Biochar Produced from Different Temperatures and Their Effects on Urine Properties and Fractions - Jinyuan Jiang; Changjun He; Haoyang Song; Wei Tan (Water, Air, & Soil Pollution, 2023)

Identification of liquors from the same brand based on ultraviolet, near-infrared and fluorescence spectroscopy combined with chemometrics - Miao He; Xiaolong Chen; Jing Zhang; Jiawei Li; Dong Zhao; Yang Huang; Danqun Huo; Xiaogang Luo; Changjun Hou (Food Chemistry, 2023)

Binding characteristics of Pb and Zn to low-temperature feces-based biochar-derived DOM revealed by EEM-PARAFAC combined with general and moving-window two-dimensional correlation analyses - Changjun He; Xuwen He; Run Yuan; Na Li; Jinyuan Jiang (Environmental Science and Pollution Research, 2022)

Genome-Wide Identification and Expression Profile Analysis of the SnRK2 Gene Family in Nicotiana tabacum - Jinghao Li; Jiangyu Song; Changjun Li; Juntao Ma; Jiawang Liu; Xiaowei Zhu; Jingchao Li; Fan He; Chao Yang (Biochemical Genetics, 2022)

How Deep Might Myoblasts Sense: The Effect of Substrate Stiffness and Thickness on the Behavior of Myoblasts - Shan Li; Feng Zhao; Yuewei Zhan; Xiaoyi Liu; Tingting Hun; Haokang Zhang; Changjun Qiu; Jingwen He; Zongchun Yi; Yan Sun; Yubo Fan (Journal of Medical and Biological Engineering, 2018)

Copper-containing mesoporous bioactive glass coatings on orbital implants for improving drug delivery capacity and antibacterial activity - Juan Ye; Jinjing He; Changjun Wang; Ke Yao; Zhongru Gou (Biotechnology Letters, 2014)